2012
DOI: 10.5812/iranjradiol.4063
|View full text |Cite
|
Sign up to set email alerts
|

Developing Criteria for Lumbar Spine Magnetic Resonance Imaging (MRI) Using RAND Appropriateness Method (RAM)

Abstract: BackgroundStudies show that a large proportion of healthcare offered may be inappropriate or unnecessary. Magnetic resonance imaging (MRI) is a new and expensive diagnostic technology which has been increasingly used all over the world. Moreover, this trend has been more rapidly increasing in Iran. Low back pain is a common disorder all over the world and MRI technique is one of the several ways to assess its cause.ObjectivesThe present study aims to develop scenarios for lumbar spine MRI.Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…8 The results of this study showed a significant association between inappropriate prescriptions and the patients' gender, with inappropriate prescriptions being higher among men than among women. This is consistent with the results by Keshtakaran et al 14 However, no significant association between inappropriate prescriptions and the patients' gender was found in the study conducted in Mashhad. 8 According to results of the present study, no significant relationship was observed between inappropriate prescriptions and the patients' occupation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…8 The results of this study showed a significant association between inappropriate prescriptions and the patients' gender, with inappropriate prescriptions being higher among men than among women. This is consistent with the results by Keshtakaran et al 14 However, no significant association between inappropriate prescriptions and the patients' gender was found in the study conducted in Mashhad. 8 According to results of the present study, no significant relationship was observed between inappropriate prescriptions and the patients' occupation.…”
Section: Discussionsupporting
confidence: 83%
“…It seems that physicians in hospitals spend more time examining patients. 14 However, in Ebrahimipour and et al in a study on inappropriate knee MRI prescriptions in Mashhad wasn't found a significant relationship between these variables. 8 The results of this study showed a significant association between inappropriate prescriptions and the patients' gender, with inappropriate prescriptions being higher among men than among women.…”
Section: Discussionmentioning
confidence: 99%
“…The research results indicated that 56.7%, 39.7%, and 3.6% of the prescriptions were appropriate, inappropriate, and uncertain, respectively. Results from other studies confirmed the inappropriate lumbar and knee MRI prescriptions in Iran . Studies previously conducted in Iran show that the inappropriate lumbar MRI prescriptions varied from 2.6% to 80% and could be attributed to differences in the clinical guidelines used, the prevalence of musculoskeletal disorders, and level of access to MRI centers in different parts of Iran .…”
Section: Discussionmentioning
confidence: 99%
“…Even though low back pain is one of the most prevalent disorders in primary care, very often, a definite diagnosis cannot be formulated early enough to either reassure the patient or to refer appropriately for non-conservative treatment options (Arnbak et al 2015, Keshtkaran et al 2012). Moreover, there is a little consensus among the specialists about appropriate low back pain procedures (Keshtkaran et al 2012). Therefore, more knowledge is required about the various causes of low back pain to improve its management (Arnbak et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more knowledge is required about the various causes of low back pain to improve its management (Arnbak et al 2016). Magnetic resonance imaging (MRI) is being increasingly used in an attempt to optimize the diagnostic process for low back pain (Arnbak et al 2015, 2016, Keshtkaran et al 2012). The ultimate benefit of an MRI depends upon the choice of treatment option given the current clinical condition and increasingly the expectations of the patient.…”
Section: Introductionmentioning
confidence: 99%